If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = 6a + -27 Reorder the terms: 9 = -27 + 6a Solving 9 = -27 + 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. 9 + -6a = -27 + 6a + -6a Combine like terms: 6a + -6a = 0 9 + -6a = -27 + 0 9 + -6a = -27 Add '-9' to each side of the equation. 9 + -9 + -6a = -27 + -9 Combine like terms: 9 + -9 = 0 0 + -6a = -27 + -9 -6a = -27 + -9 Combine like terms: -27 + -9 = -36 -6a = -36 Divide each side by '-6'. a = 6 Simplifying a = 6
| 2k^2+9=-7 | | (9x-2)(9x-2)= | | 5-8X=55-43X | | (T)(3)=-15 | | -91-10X=9X+23 | | A=ax(2)+bx+c | | 6X+5=-125-7X | | 7b+3(b-1)+3=2(b+18) | | -41-3x=8-10x | | 16x^4-20x^2+5=0 | | 6x^2-600=0 | | 5x=7x-10 | | 2x^2-15x-8=0 | | 6x+7=5x+15 | | -8-9=-8(x-9) | | 64x-1=0 | | 2x+107=10x-5 | | 2x^6+4x^5-6x^4+4x^3= | | 4x-y=-1 | | 73-3x=15x+17 | | 3x-4(1-x)=4+5x | | 15x^2+27x-2=0 | | 8(x+2)-10=3(2x-1)+9 | | 12b-8= | | 11x-8x=156-43x | | 3-3x-2(1-x)=7(x-4)+29 | | -152-9x=8x+18 | | x-0.3x= | | 10x+15=4x+165 | | 6x+6=-59-7x | | 8x-5=4x-1 | | 2x+57=7x+12whatisx |